The Romance of Democracy : Compliant Defiance in Contemporary Mexico - Gutmann, Matthew C., 1953- (Book collections on Project MUSE., 2002)
The Romance of Democracy gives a unique insider perspective on contemporary Mexico by examining the meaning of democracy in the lives of working-class residents in Mexico City today. A highly absorbing and vividly detailed ethnographic study of popular politics and official subjugation, the book provides a detailed, bottom-up exploration of what men and women think about national and neighborhood democracy, what their dreams are for a better society, and how these dreams play out in their daily lives. Based on extensive fieldwork in the same neighborhood he discussed in his acclaimed book The.